The Effect of 7E’s Learning Cycle Model in Teaching Science on the Achievement and the Development Basic Science processes of the First Grade Intermediate Female Students in Asser region - Abdullah, Hind bint Mohi (Journal of Educational and Psychological Sciences, 2019)
The study aimed to identify the impact of the seven- cycle learning model in teaching science on the achievement and development of the basic science processes of the first grade students. To achieve this goal, the research adopted descriptive and semi- experimental approaches. The experiment was applied to a random sample of (88) female students of the first grade intermediate in the Eighteenth Middle School for Girls in Abha, Department of Education in Asir region, (46) students who studied the "nature of the material" module using the seven- cycle learning model and the other 42 female students who studied the same unit in the usual way. At the end of the experiment, both tests were applied periodically to both groups. In the first semester of the academic year 1436 AH, and the results of the study indicated that there are statistically significant differences at the level (0.05) between the averages of the students of the experimental and control groups in the post- application of the achievement test and test the basic science processes in science for the benefit of the experimental group, Use of themes Seven learning in the teaching of science course had an impact on an acceptable educational attainment and development of basic science processes among students average first grade, and in the light of those findings, were some recommendations and proposals.